Rancangan Perbaikan Beban Kerja Staf di Departemen Purchasing PT Insera Sena - Yuwono, Joan; Palit, Herry Christian (Jurnal Titra, 2014)
Process of bicycleâs raw materials procurement in PT Insera Sena is handled by Purchasing Department. The problem in the Purchasing Department is employeeâs workload at the level of Purchasing head and staff is not balanced. Workload among employees during observation is between 72.56% to 117.46% with average of workload is 97.05%. The evaluation shows that activity performed by Purchasing head and staff are not according to job description and work procedures. Some improvement plans are simulated and workload is between 82.85 % to 99.92 % with average of workload is 92.46 %. These improvement plans can save Rp 10.906.711,11 per year with assumption the minimum wage of Sidoarjo in 2013 is about Rp 1.720.000,00.